Investigating the Causal Relationship between Fossil Fuels Consumption and Economic Growth at Aggregate and Disaggregate Levels in Saudi Arabia - Alshehry, Atef Saad; Belloumi, Mounir (International Journal of Energy Economics and Policy, 2014)
This paper studies the causal relationships between fossil fuels consumption, CO2 emissions and economic activity at aggregate and disaggregates levels in Saudi Arabia using the multivariate cointegration approach. The results show the existence of a long-run equilibrium relationship between fossil fuels consumption, carbon dioxide emissions and economic growth. Moreover, in the long-run the causality is unidirectional running from economic growth to energy consumption and natural gas consumption whereas there is absence of causality in the case of oil consumption. Our results indicate that energy conservation policies might be enforced without affecting economic growth. Policies aimed at reducing fossil fuel consumption and controlling for CO2 emissions may not affect negatively Saudi’s economic growth. Hence, policy reforms aimed at reducing fossil fuels (oil and natural gas) subsidies become an urgent necessity in the near future in order to eliminate fossil fuel wastes. Keywords: Oil consumption; natural gas consumption; economic growth. JEL Classifications: C32; Q43.